(untitled) (Jurnal Destinasi Pariwisata, 2025)
This research study focuses on restaurants which area commercial business that provides food and beverage services for the public and is managed professionally. The restaurant studied is a restaurant located in a hotel environment and provides local cuisine as an attraction for tourists who stay at starred hotels in Badung Regency. The variety of restaurants that are growing and developing today needs to identify the types of local culinary dishes, tourist characteristics, factors that encourage tourists to choose local cuisine and tourist perceptions of the adaptation of local cuisine. This research was conducted through descriptive interpretative and qualitative studies and quantitative descriptive statistics with a Likert scale. The sample in this study used the Purposive technique and Quota sampling technique referring to J. Supranto opinion. The data collection techniques used were observation, questionnaires, interviews and documentation. Tourist characteristics are dominated by tourists from Asia, unmarried status with male gender and type of worker as a student with undergraduate education level. Types of dishes consist of appetizers in the form of mixed vegetables and Jackfruit Salad. Soup dishes consist of Ares Vegetables, Balinese Chicken Soup, Fish Soup while the main dishes include Betutu Chicken , Sate lilit, Pesaan, Suckling Pig, Be Pasih sambel Matah. Desserts consist of bubuh injin, batun bedil, Fried Banana and jaja klepon. Tourist motivation with intrinsic motivation of curiosity as a factor and Extrinsic factors in the form of its location in a tourist area with a strategic position. Tourist perceptions of local culinary adaptation received the lowest rating, namely the variety of local culinary menu choices offered, and for aspects of product quality, price suitability and quality of waiter service with a good category.